An empirical phenomenological investigation of procrastinating behaviour - Barratt, Neal Anthony (Rhodes University, Faculty of Humanities, Department of Psychology, 2010)
A qualitative empirical phenomenological study was undertaken to determine the self-experience of procrastinating behaviour. Five students each gave an account of an occasion when they procrastinated. The resultant protocols were analysed and the Situated Structure of each individual's experience was reported. From these, the General Structure of procrastinating behaviour was determined. A further, novel step was added to the standard methodology, whereby 'themes' were extracted from participant protocols and a 'Composite Reality' of everyday-life procrastination was rendered. Participants' accounts suggest they are concerned the results of intellectual tasks they undertake will be seen as equivalent to their quality of being-as-an-individual: poor work results will be interpreted by important-others as evidence of participants' poor quality of self "“ which is to be avoided. This study suggests that procrastination is a ploy used by individuals to avoid criticism, by deflecting assessment of their capacity to complete a task well, to instead, what they are capable of when only a limited time is available. Conclusions drawn by the important-others of participants' true ability are thereby confounded. The results achieved in the phenomenological study were compared with others originating from various quantitative studies, and considerable overlap was found. The experiential richness of the phenomenological results point to a worthwhile methodological strategy for future procrastination research.
Keywords: Procrastination; Self-actualization (Psychology); Cognitive psychology